Berlin - Hauptstadt der DDR - Maetzig, Kurt; Hadaschik, Joachim; Belz, Uwe; Machalz, Alfons; Meinl, Trutz; Richardt, Ellen; Böttcher, Jürgen (Icestorm, 2021)
Original-Dokumentationen der DEFA aus den Jahren 1946 bis 1986 rund um Berlin, die Hauptstadt der DDR. [www.jakob.de]
Keywords: DVD-Video